Influência do tratamento térmico nas propriedades mecânicas de resinas compostas - Henke, Patrícia Graziela (2013)
The aim of this study was to evaluate the influence of heat treatment on the flexural strength and diametral tensile composite resins. We selected five brands of composite resins for direct use (Filtek® Z250, 3M ESPE, Filtek® Z350®, 3M ESPE, Charisma®, Heraeus Kulzer; Opallis®, FGM; Evolu-X®, Dentsply) and indirect use (Solidex®, Shofu), as a standard of comparison. With each composite were prepared 16 specimens (sps) (6mmx4mm) for the diametral tensile test and 16 sps (10mmx2mmx1mm) for testing flexural strength of three points. The sps were randomly divided in two groups: control group (storage in water at 37 º C for 24 hours) and treatment group (heat treatment by the application of dry heat at 170 ° C for 10 minutes). After the sps were subjected to mechanical testing in a universal testing machine. The transformed data in Mega Pascal (MPa) were submitted to ANOVA and Turkey test (5%). The effect of heat treatment was observed depending on the composite resin and mechanical testing and, when present, increased the resistance between 8 and 23%. The differences between the resins were more evident in the bending test. Significant correlation was found between tests (Pearson's r = 0.6, p> .01). Conclude that the effect of heat treatment on mechanical strength of composite resin material and depends on the assay used.